Credit allocation of Japanese banks in the 1990s: Evidence from the short-term economic survey of enterprises - Kazuo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
This study is an empirical attempt to investigate the effects of balance sheet deterioration of Japanese firms and banks during the 1990s on credit allocation using the Short-term Economic Survey of Enterprises. This survey includes a unique item: the proportion of firms perceiving the lending attitude to be severe. After developing a theoretical model to link this item with the balance sheet conditions of borrowers and lenders, we estimated the relationships that we derived from our model. We found that credit was reduced when the balance sheet of firms and banks deteriorated. The effects are particularly significant for non-manufacturing industries.
Keywords: E44; E51; G21; 330; Tankan Survey; Credit crunch; Ever-greening; Non-performing loans; Corporate Debt; Kreditgeschäft; Kredit; Verbindlichkeiten; Theorie; Schätzung; Japan